Metasomatism and Hydration of the Oceanic Lithosphere: a Case Study of Peridotite Xenoliths from Samoa. (18th February 2020) - Ashley, Aaron Wolfgang; Bizimis, Michael; Peslier, Anne H; Jackson, Matthew; Konter, Jasper G
Abstract: Water influences geodynamic processes such as melting, deformation and rheology, yet its distribution in the oceanic upper mantle is primarily known indirectly from melt inclusions and glasses of erupted mantle melts (i.e. mid-ocean ridge and ocean island basalts). To better constrain the mechanisms influencing the distribution of H2 O in the mantle, particularly regarding the role of metasomatism, we analyzed 15 peridotite xenoliths from Savai'i and two dunite xenoliths from Ta'ū (Samoa) for structural H2 O (by polarized Fourier transform infrared spectroscopy), and major and trace element concentrations. Clinopyroxenes from the Ta'ū dunites show trace element concentrations consistent with equilibration with their host lavas, but lower H2 O contents than expected. Savai'i peridotites are highly depleted harzburgites (melt depletion ≥17 %). They show strong evidence of transient metasomatism by both carbonatite and silicate melts, with highly variable Ti and Zr depletions and light rare earth element enrichments. However, despite metasomatism the H2 O concentrations in olivines (0 − 4 ppm H2 O) and orthopyroxenes (17 − 89 ppm H2 O) are among the lowest reported in oceanic xenoliths, but higher than expected for the estimated degree of depletion. In general, H2 O concentrations vary less than those of other incompatible trace elements in these samples. Transects across mineral grains show generally homogeneous distributions of H2 O, indicating no significant H2 O loss or gain during ascent. Raman spectroscopy on inclusions in minerals shows the presence of CO2 but an absence of molecular H2 O. This agrees with the absence of H2 O concentration variations between inclusion-rich and -poor domains in minerals. The above data can be explained by transient metasomatism along grain boundaries, now recorded as planes of inclusions within annealed grains. Fast diffusion of hydrogen (but not lithophile elements) from the inclusions into the host mineral phase will simultaneously enrich H2 O contents across the grain and lower them in the inclusion-rich domains. The result is highly variable metasomatism recorded in lithophile elements, with smaller magnitude H2 O variations that are decoupled from lithophile element metasomatism. Comparison with xenoliths from Hawai'i shows that evidence for metasomatism from lithophile elements alone does not imply rehydration of the oceanic lithosphere. Instead, H2 O concentrations depend on the overall amount of H2 O added to the lithosphere through metasomatism, and the proximity of sampled material to areas of melt infiltration in the lithosphere.